The complement system and its role in the pathogenesis of periodontitis: current concepts. (5th July 2014) - Damgaard, C.; Holmstrup, P.; Van Dyke, T. E.; Nielsen, C. H.
Abstract : Periodontitis is a highly prevalent inflammatory disease in tooth supporting tissues, induced by bacteria growing in a biofilm on tooth surfaces. Components of the complement system are present in the periodontal tissue and the system is activated in periodontitis. Continuous complement activation and modulation by bacteria within the biofilm in periodontal pockets, however, may enhance local tissue destruction, providing the biofilm with both essential nutrients and space to grow. A more profound understanding of the mechanisms involved in complement‐derived tissue degradation may facilitate the development of new treatment concepts for periodontitis. Further studies on the role of complement in periodontitis pathogenesis may also contribute to the understanding of why some individuals fail to resolve periodontitis. Here, we review evidence that links complement to the pathogenesis of periodontitis with an emphasis on interaction of complement with bacteria from periodontitis‐associated biofilm.